Does Foreign Direct Investment Replace Home Country Investment? The Effect of European Integration on the Location of Swedish Investment - Pontus Braunerhjelm; Lars Oxelheim (The Research Institute of Industrial Economics (IUI), 1999)
The purpose of this paper is to examine the effects of European integration on the location of investments by Swedish multinational corporations (MNCs). Evidence is presented about the extent to which European integration has attracted investment by Swedish MNCs, and whether foreign direct investment is being undertaken at the expense of home country investment. In the empirical analysis, involving both OLS and iterative SUR techniques, a significant difference across industries has been confirmed. A substitutionary relationship between foreign and home country investment is found for more R&D-intensive production, whereas the opposite pattern seems to prevail for production based on traditional comparative advantage. The results of this study emphasize the importance of using disaggregated industry-level data when analysing the effects of foreign direct investment on home country investment.
Keywords: F12; F23; 330; Foreign direct investment; Home country investment; regional integration; Substitutionary; Schumpeterian; Auslandsinvestition; Verdrängungseffekt; Eurozone; Betriebliche Standortwahl; Schweden; Investition